Financial Inclusion of Women in Slums in Chandigarh through Pradhan Mantri Jan Dhan Yojna - Bansal, Ajit; Aggarwal, Pranav; Singh, Manpreet; Ramgopal (International Journal of Psychosocial Rehabilitation, 2020)
The main decisive constriction for overall and sustainable development of the economy is that a large number of unprivileged and poor people don’t have access to the recognized financial system of the nation. Thus, for achieving the goal of sustainable economic development and for being an economic superpower, financial inclusiveness has been given due importance by economists and policymakers. Pradhan Mantri Jan Dhan Yojana (PMJDY) is launched by the Honorable Prime Minister of India, Shri Narendra Modi, on 28th August, 2014. The critical goal of the scheme is to offer admittance to the banking system, including zero-balance savings bank accounts, overdraft facilities up to Rs.5000/-, RuPay debit cards with accidental indemnity cover, and RuPay Kisan Cards. The key objective of this research is to examine the standing of fiscal involvement of females in slums of Chandigarh after five and a half years of the formal launch of the said scheme. A survey was conducted during November 2019-December 2019 covering all slum areas of UT Chandigarh by administering a questionnaire to 150 respondents. The examinations revealed that women from slums have linked official banking procedures independently of their edification level, owing to awareness regarding PMJDY. It is also observed that still money lenders are part of the financial system.